Keep the memories, lose the stuff : declutter, downsize, and move forward with your life - Paxton, Matt; Smith, Jordan Michael (Portfolio/Penguin, 2022)
"America's top cleaning expert and star of the hit series Legacy List with Matt Paxton distills his fail-proof approach to decluttering and downsizing. Your boxes of photos, family's china, and even the kids' height charts aren't just stuff; they're attached to a lifetime of memories--and letting them go can be scary. With empathy, expertise, and humor, Keep the Memories, Lose the Stuff helps you sift through years of clutter, let go of what no longer serves you, and identify the items worth keeping so that you can focus on living in the present. For over 20 years, Matt Paxton has helped people from all walks of life who want to live more simply declutter and downsize. As a featured cleaner on Hoarders and host of the Emmy-nominated Legacy List with Matt Paxton on PBS, he has identified the psychological roadblocks that most organizational experts routinely miss but that prevent so many of us from lightening our material load. Using poignant stories from the thousands of individuals and families he has worked with, Paxton brings his signature insight to a necessary task. Whether you're tired of living with clutter, making space for a loved one, or moving to a smaller home or retirement community, this book is for you. Paxton's unique, step-by-step process gives you the tools you need to get the job done"--